2003
DOI: 10.1002/cbf.1050
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium release is required for caspase‐3 and ‐9 activation

Abstract: Increase in intracellular Ca2+ [Ca2+]i regulates many biological functions including apoptosis, but the protein(s) linking [Ca2+]i and apoptosis are not completely understood. We have previously shown that IP3R-deficient cells are resistant to T-cell receptor (TCR)-induced apoptosis due to lack of Ca2+ release from endoplasmic reticulum (ER) and calcineurin activation. Here we show that caspase-9 and -3 are not activated in IP3R-deficient cells after TCR stimulation, consistent with the resistance of these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 19 publications
3
24
1
Order By: Relevance
“…Overall, our data confirm the idea that membrane destabilization by the aggregates and the subsequent early modifications of ion balance and intracellular redox status may trigger subsequent modifications eventually leading to cell death (Mattson, 1999;Kruman et al, 1999;Kawahara et al, 2000;Gennady and Kelvin, 2001;Milhavet and Lehmann, 2002;Hyun et al, 2002;Mattson and Liu, 2002;Kayed et al, 2003;Tantral et al, 2004;Bucciantini et al, 2004;Bucciantini et al, 2005). In this context, we have found that membrane cholesterol may play a key role in disfavouring aggregate absorption to the plasma membrane thus triggering the cascade of events eventually leading to cell death.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, our data confirm the idea that membrane destabilization by the aggregates and the subsequent early modifications of ion balance and intracellular redox status may trigger subsequent modifications eventually leading to cell death (Mattson, 1999;Kruman et al, 1999;Kawahara et al, 2000;Gennady and Kelvin, 2001;Milhavet and Lehmann, 2002;Hyun et al, 2002;Mattson and Liu, 2002;Kayed et al, 2003;Tantral et al, 2004;Bucciantini et al, 2004;Bucciantini et al, 2005). In this context, we have found that membrane cholesterol may play a key role in disfavouring aggregate absorption to the plasma membrane thus triggering the cascade of events eventually leading to cell death.…”
Section: Discussionsupporting
confidence: 86%
“…intracellular stores plays a critical role in modulating the activity of caspase-3/CPP32, whose activated form can, in turn, affect free Ca 2+ levels by cleaving membrane calcium pumps (Tantral et al, 2004). Our results confirmed such a close crossdependence; in fact, following 24 hours exposure to the aggregates, all investigated cell lines displayed a positive correlation between the rise of free Ca 2+ and the content of the caspase-3 active fragment ( Table 1).…”
Section: Apoptotic and Necrotic Markerssupporting
confidence: 79%
“…Recently, a multitude of calcineurin effectors, both transcriptional and nontranscriptional, have been identified. These include not only proteins that target the nucleus as transcriptional regulators (54) but also factors that affect a host of functions including ribosomal biogenesis (55), apoptotic (56), and mitochondrial pathways (57)(58)(59). The latter is of particular interest because previous studies in both acinar (14,15) and ductal cells (60) suggest that bile acids impair mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that a requirement for IP 3 Rs in obtaining optimal rates of apoptosis can be observed by monitoring the levels of caspase-3 activation. Thus, TKO DT-40 cells [20,98] and T-cells deficient in the type-I IP 3 R [99] have low rates of caspase-3 activation in response to an apoptotic stimulus when compared to the wild-type cells. In TKO DT-40 cells a non-phosphorylatable S2618A mutant was able to support almost 3.5-fold higher caspase-3 activation than the phosphomic S2618E which behaves similarly to wild-type receptors [95].…”
Section: Regulation By Akt-kinasementioning
confidence: 96%